PENGARUH PENGGUNAAN CUSTOM INSOLE TERHADAP AGILITY PADA ANAK UMUR 8-12 TAHUN - Muhibbah Fatati; Dwi Setyawan (Tahta Media Group, 2025)
Background: The foot is a very important part of the limb for walking, and functions as a lever so that the foot is the part that receives the deformity force, so the shape of the sole of the foot has a very important role in carrying out every physical activity. The description above provides an illustration that someone with a flat foot shape has a physical activity ability, namely agility, which is less good compared to someone who has a normal foot shape. Methods and Subjects: The method used in this study is quantitative experimental using a Randomized Controlled Trials (RCT) research design. This study uses a single blinding method where the research subjects do not know what type of insole they are using. The randomized technique in this study uses simple randomization, namely by drawing lots. The sample of this study was 38 respondents, where the control group and the intervention group received the same treatment by being given standard treatment in the form of custom insoles but for the control group they were given regular insoles without medial arch support (MAS). And the intervention group was given insoles with medial arch support (MAS) features. Therefore, in this study, a pre-treatment test was conducted as a basis for determining the level of sample homogeneity, as well as a post-treatment test which was used as data to compare the effectiveness of the intervention between the two groups tested. The measuring instrument used in this study was the Edgren Side Step Test (ESST). Results: The results of the Mann Whitney test showed that there was a difference in the average agility between the intervention group (16.52) and the control group (17.73) with a p value = 0.042 where the p value <0.05.Conclusion: The conclusion of this study is that there is a statistically significant difference in agility in the intervention group and the control group. Where the intervention group has better agility than the control group